EPISTEMOLOGI FIQH DAN KONTRIBUSINYA BAGI PENEGUHAN SPIRIT GENDER - Bahagia, Moh. Rasyid; Bahagia, Asyfiyah Fitriani (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2020)
This article specifically describes the fiqh epistemoloqy as a new perspective in analyzing how Islam views gender equality.  Through fiqh epistemoloqy, which consists of three subdivions of reasoning: bayani, ta'lili, and isthilahi, the author analyzes how the construction of gender in Islam, which has been taken from its detailed dalils. The result of author's analysis shows that each three reasonings have their own tendency and influence toward the construction of gender spirit edification. Among the three fiqh espitomoloqy reasonings, only bayani reasoning is not quite relevant in analyzing gender-based religous texts. Gender is a social construct that involves roles and values that can be pinned on both female and male who, therefore, a gender-based dichotomy is not naturally stuck in human beings from birth. Islam places people in the same level not only to create a fair, affluent, and prosperous social order, but also because gender-based discrimination is a contraproductive form of dehumanization with the normative doctrine of islamic law. To reject the concept of gender is like opposing Islam's strategy as theological legitimacy over the concept of gender. The good and bad of humans in Allah's side, is not determined by whether he is male or female, but it is determined by the quality of his worship and obedience.